The Employee Productivity in Micro Enterprises: a study of SMEs in the agricultural sector: - - Tri Sugiarti Ramadhan; Agus Hermawan; Naswan Suharsono (Cita konsultindo, 2023)
This research aims to determine the influence of motivation, work discipline and compensation on the productivity of SME employees in the agricultural sector. The data used in this research uses primary data through distributing questionnaires to respondents and secondary data to determine the monthly production capacity carried out by agricultural sector employees. The population in this study were Setia Mamur employees, while the sample in this study consisted of 40 respondents, all of whom were Setia Makmur employees in Malang district. The data analysis method used in this research is multiple linear regression analysis, with the SPSS 25 analysis tool. This research shows that motivation has no effect on employee productivity, work discipline has an effect on employee productivity, and compensation has an effect on employee productivity.